Estudio de factibilidad para la implementación de un centro de acopio para el almacenamiento y conservación de frutas y hortalizas cantón Quevedo - Páez Paredes, Digna Isabel (2013)
The Quevedo canton is one of the leading and fastest growing cities being substantial part in socio-economic development of the province of Los Rios in her series of micro production, marketing and service them to play a role are settled very important in the Ecuadorian economy, so that small businesses engaged in trade of fruit and vegetables have increased significantly to meet local demand and contributing to the economy. This research study was conducted with the main objective of implementing a storage facility for the storage and preservation of fruits and vegetables in the canton Quevedo, the same is made for the execution of market research, the realization of the technical study, and finally determine the financial evaluation………………